2020
DOI: 10.1016/j.bbi.2020.05.048
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and mental health consequences: Systematic review of the current evidence

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

167
2,416
16
160

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 2,753 publications
(2,759 citation statements)
references
References 86 publications
167
2,416
16
160
Order By: Relevance
“…Infectious diseases outbreaks are known to have health, social and economic implications, for infected and non-infected persons alike. Prior studies have shown the adverse psychological impact of COVID-19 and its containment measures in COVID-19 patients, frontline workers, patients with pre-existing psychiatric diseases and the general population [8,9]. Our ndings are consistent with prior literature, and further extended those reports by providing the perspectives of those with CVD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Infectious diseases outbreaks are known to have health, social and economic implications, for infected and non-infected persons alike. Prior studies have shown the adverse psychological impact of COVID-19 and its containment measures in COVID-19 patients, frontline workers, patients with pre-existing psychiatric diseases and the general population [8,9]. Our ndings are consistent with prior literature, and further extended those reports by providing the perspectives of those with CVD.…”
Section: Discussionsupporting
confidence: 89%
“…Pandemics are known to affect infected and non-infected persons in a myriad of ways. Studies evaluating the impact of COVID-19 on non-infected persons have focused largely on the psychological consequences [8,9]; both small and large studies have been conducted in general population, healthcare workers, and those with pre-existing psychiatric diseases. Little is known about the impact of COVID-19 on physical and mental health of patients with CVD.…”
Section: Introductionmentioning
confidence: 99%
“…38 A recent systematic review evaluating the impact of the COVID-19 pandemic on mental health outcomes, including MWB, concluded that a lower psychological well-being was noted among females and those who self-reported a poor health. 15 In fact, vulnerable people, particularly those with chronic diseases, require special attention. Around 20% of our respondents had a chronic disease and exhibited a lower MWB in the whole group and the workers' subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Lebanon has high percentages of vulnerable populations, such as elderly, 41 and chronic diseases, [42][43][44] considered at higher risk for COVID-19 and lower MWB. 15,45 Reasons in this context could include panic due unreliable information for patients, 46 especially in an era of massive misinformation in the media, 47,48 added to the economic situation itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation